The “Pearls” of Multidisciplinary Team: Conquering the Uncommon Rosette Rash - Nitin Verma; Charles Pickles; Muhammad Amjad Khan (Case Reports in Pediatrics)
Linear IgA disease of childhood (LAD) also known as chronic bullous disease of childhood is an autoimmune disease with IgA deposition at the basement membrane zone leading to a vesiculobullous rash. It has a clinical appearance which frequently is described as resembling “strings of pearls” or rosette-like. Diagnosis is usually clinical but sometimes biopsy is required. Dapsone is widely considered to be the first line therapy in the treatment of LAD. A 5-year-old girl presented with 4-day history of a widespread painful rash and pyrexia. The rash transformed into painful blisters. A recent contact with chickenpox was present. She remained apyrexial but hemodynamically stable and was treated as chickenpox patient with secondary infection. Due to persistent symptoms after repeated attendance she was reviewed by Dermatology team and diagnosed with linear IgA disease also known as chronic bullous disease of childhood. This was based on the presence of blistering rash with rosette appearance and string of pearl lesions. The clinical features of LAD can be difficult to distinguish from more common skin infections. Benefiting from the experience of other multidisciplinary teams can sometimes be a game changer and can lead to the correct diagnosis and treatment.